International tours of theatre as a means of intercultural cooperation - Meilutė, Ieva; Jurėnienė, Virginija (Information & Media, 2020)
The 21st century theatre is open to new ideas, new findings and presentation of own works to the consumer on not only the national, but also international level. This stands for communication and cooperation with the consumer and organisations. Theatre tours abroad are one of the forms of intercultural cooperation among organisations and consumers. The article analyses the peculiarities of organising theatre tours, its benefit and levels of cooperation. The study includes an analysis of organising national and commercial theatre tours on an international level which allows concluding that intercultural cooperation can occur on the following three levels: interpersonal (micro), interinstitutional (macro) and international (mezzo). The study reveals another new – mixed – level; however, a new mediating element can be seen in cooperation on micro or macro levels. Both types of theatre (state and non-state) see evident benefit of international tours for the theatre, the troupe and the country. A country can use this as a means of soft power in its foreign policies.
Keywords: theatre; tours; organizing; intercultural cooperation; benefit